Análise paramétrica da microvascularização encefálica com perfusão por ressonância magnética na diferenciação entre lesões infecciosas e neoplásicas - Floriano, Valdeci Hélio (2013)
INTRODUCTION: Brain perfusion studies by magnetic resonance imaging (MRI) may be performed as a complementary non-invasive examination to conventional MRI, thus providing data on hemodynamic parameters, including the degree of angiogenesis of lesions. OBJECTIVE: To employ perfusion-weighted MRI to differentiate between infectious and neoplastic brain lesions by investigating changes in the brain microcirculation. PATIENT AND METHOD: Perfusion-weighted MRIs of one hundred 18- to 84-year-old patients with non-cortical lesions were retrospectively assessed: primary and secondary neoplasms confirmed by pathological investigations (n = 54) and infectious lesions identified by an analysis of cerebrospinal fluid and therapeutic test (n = 46). The relative cerebral blood volume (rCBV) was measured in the solid areas of lesions and compared with rCBV values obtained in contralateral white matter of normal appearance. RESULTS: On using an rCBV ≤ 1.3 as the cutoff to define infectious lesions, the sensitivity of the test was 97.8% (lower 95%CI: 88.5%) and the specificity was 92.6% (95%CI: 82.1% - 97.9%) with a positive predictive value of 91.8% (95%CI: 80.4% - 97.7%), negative predictive value of 98.0% (lower 95%CI: 89.5%) and an accuracy of 95.0% (95%CI: 90.7% - 99.3%). CONCLUSION: Perfusion-weighted MRI had discriminatory value for diagnosis of infectious brain lesions when the value of the rCBV was ≤ 1.3.